PENGARUH KUALITAS PRODUK DAN SISTEM INFORMASI PEMASARAN TERHADAP PENINGKATAN PERMINTAAN DI PT. WAHANA TRANS LESTARI MEDAN - Bagus Handoko (Universitas Islam Islam Sumatera Utara, 2021)
Every company must have a desire to be successful in marketing all products, both goods and services. This success can be achieved by setting the cost price correctly. Product is one element of the marketing mix in addition to the other three elements (price, distribution, and promotion). Marketing information system is a set of information elements that have been prepared, arranged systematically to become a complete data in order to fulfill / support the activities of the organization and managers in general. From the description above, the authors formulate the problem: